Do Ends Justify Means? Feminist Economics Perspectives on the Business Case for Gender Equality in the UK Labour Market - Emily Thomson (e-cadernos ces)
This paper intends to explore a feminist economics perspective on business case arguments for gender equality in the UK labour market, where there are significant inequalities between men and women. Policy discourse on gender equality has moved from one which emphasises ‘equal opportunities’ and notions of fairness and equal treatment to one which focuses on increasing economic efficiency in the wider economy and viewing female employees as a competitive advantage for individual firms. Developments in the policy discourse of gender equality in the labour market have been heavily influenced by mainstream, neoclassical economics. An example of this is the current UK government aim to encourage private sector employers to take action on gender equality voluntarily on the basis of ‘business case’ arguments. The business case itself has been critiqued by many authors but has yet to be considered from an explicitly feminist economics perspective. Feminist economics is argued to be a more appropriate paradigm for the consideration of gender inequalities.